Anti-Social Networking: Findings From a Pilot Study on Opposing Dudley Mosque Using Facebook Groups as Both Site and Method for Research. (30th January 2014) - Allen, Chris
With research highlighting the growing incidence of public opposition to the building of mosques and the innovative use of social networking, especially Facebook, to disseminate and garner support for such opposition, a pilot study sought to investigate this in relation to the proposed Dudley "super mosque." Focusing on the Facebook group Stop Dudley Super Mosque and Islamic Village, members were engaged online to explore why they opposed the mosque. Some of the emergent themes included planning and location, inclusion and public investment as well as those relating to notions of identity, heritage, otherness, and Islamification. Overt racist and Islamophobic reasons were also identified. The sense of political disconnect of members is also considered. Concluding with a contextualization of the findings within the existing body of scholarly output, in particular the building of mosques and Islamophobia, having recognized how spaces such as Facebook have potential to function as sites for research and method also, an extended methodological consideration is also included.